BUROCRATIZAÇÃO NO NEOLIBERALISMO: AMBIVALÊNCIAS NA IMPLEMENTAÇÃO DAS POLÍTICAS EDUCACIONAIS BRASILEIRAS A PARTIR DOS ANOS 1990 - Locatelli, Cleomar (2009)
This paper aims at analyzing the changes experienced by local bureaucracies in policy development of education policies, in view of the neoliberal guidelines adopted by the Brazilian State from the 1990s, in the context of the determinations of the productive restructuration and of the globalization processes. It conducts a study on bureaucracy in the capitalist State, in its double dimension: State devices and personifications, as a contradictory and historically determined phenomenon. It gathers empirical data concerning both the development of education policies in Brazil, as well as its management by local governments, and the municipal education systems in Tocantins state Region of the Bico do Papagaio , focusing the conditions under which the managerial innovations are situated, oriented in the current frame of the capitalist system of production. It concludes that the changes experienced by local public bureaucracies in the process of implementation of educational policies, considering objective and subjective aspects, as well as time and space, express in an ambiguous way, not corresponding to an automatic application of neoliberal principles. Thus, it shows that the structure of the bureaucratic machine is in beyond the immediate education policies.